Conciliationism and the Menace of Scepticism - Machuca, Diego Emanuel (2015)
It is sometimes claimed that conciliatory views on disagreement ultimately lead to either global or widespread scepticism. This is deemed to be a real problem for conciliationism either because scepticism of either kind is patently untenable or because it poses a serious threat to our intellectual and social lives. In this paper, I first argue that the alleged untenability of both types of scepticism is far from obvious and should therefore be established rather than taken for granted. Then, I show that those who reject both types of scepticism because of the threat they pose surprisingly confuse pragmatic reasons with epistemic reasons.